Documentary Film Video Games as A Learning Medium to Increase Awareness of Climate Change - Khoesasi, Winsen; Wibowo, Tony; Suwarlan, Stivani Ayuning (Visual Heritage: Jurnal Kreasi Seni dan Budaya, 2025)
Climate change is a serious problem that poses a serious threat to all people on earth. As is well known, the increasing phenomenon of global warming has led to climate change, which negatively affects all aspects of human life. As a response to these global threats, in 2015, world leaders agreed on the 2030 Agenda for Sustainable Development, which includes 17 Sustainable Development Goals (SDGs). The SDGs cover many aspects of life, especially education, health, gender equality and combating climate change. traditional education approaches tend to fail in engaging diverse audiences, leaving the individuals feeling disconnected from climate change realities. Video games have become effective learning tools in a variety of educational contexts.The use of games in education, known as game-based learning, leverages the engaging and interactive nature of games to enhance the educational experience. Documentary films about video games can be used to teach different aspects of sustainability and climate change in an interactive and fun way. The method employed in this research is the Multimedia Development Life Cycle (MDLC). This method was selected and utilized in the design process of the documentary video film because it involves multimedia elements such as text, images, videos, and animations, making it suitable for processing using this approach. The video provided allows people to develop their understanding deeper from various learning resources. When people provided various resources, especially students, they are able to enrich their understanding. However, ongoing research into the long-term impacts of multimedia on learning outcomes is crucial. Understanding how multimedia influences attitudes and behaviors over time can inform future educational strategies and game designs. Through the act of examining the effectiveness of different multimedia elements, educators and developers can create increasingly effective tools that resonate with learners and drive positive change.